Analisis Interaksionisme Simbolik Masyarakat Maya Terhadap Wacana Agama di Media Sosial Facebook - Wibowo, Arif (FIKRAH, 2018)
This study aims to find out the symbols and it is meanings in social interaction on religious discourse on Facebook. Sociological approach used to achieve the object of study. To analyse the data G.H Mead symbolic interactionism use as analysis tool. Objects on this study are some religious Facebook status. Data retrieval is done by observing some Facebook user status. The result shows that the meaning of symbols in interaction about religious discourse on social media on Facebook is very diverse, this is certainly influenced by different backgrounds and points of view. This research is so important to be used as a reference in making decisions related to regulation about the use of social media in the community.